Role of Psychosocial Factors In Vicarious Traumatization: A Comparative Study - Nazia Mustafa; hina Iqbal (Gandhara University, 2022)
OBJECTIVES: The present study aimed at investigating the role of psychosocial factors such as, gender, marital status, profession, and personal history of trauma in vicarious traumatization (VT). METHODOLOGY: Cross sectional study was conducted at various hospitals in Rawalpindi and Islamabad over the period of 6 months from January 2018 to June 2018. A sample of 170 healthcare professionals (doctors=39, psychiatrists=27, psychologists=36, nurses=30 and others=38) (men=67, women=103) was taken from various hospitals in Rawalpindi and Islamabad. Data were collected by using the Secondary Traumatic Stress Scale. RESULTS: Results revealed significant differences have been found among various groups of healthcare professionals (doctors, psychiatrist, psychologists, nurses and others) in whom psychiatrists are the most vulnerable group for vicarious traumatization and psychologists are the least vulnerable group. Moreover, healthcare professionals who are married and have personal history of trauma are more vulnerable for vicarious traumatization as compared to those who are unmarried and without personal history of trauma. No significant gender differences have been found among health care professionals on vicarious traumatization. CONCLUSION: The findings of present research have emphasized that vicarious traumatization must be addressed and identified in a health setting.